2006
DOI: 10.1016/j.jfa.2005.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly nonsquare Banach spaces have the fixed point property for nonexpansive mappings

Abstract: It is shown that if the modulus X of nearly uniform smoothness of a reflexive Banach space satisfies X (0) < 1, then every bounded closed convex subset of X has the fixed point property for nonexpansive mappings. In particular, uniformly nonsquare Banach spaces have this property since they are properly included in this class of spaces. This answers a long-standing question in the theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 21 publications
(19 reference statements)
0
37
0
Order By: Relevance
“…This result is related to the result of the paper by J. Falset et al 2006 by giving the examples and the motivation to find the geometric properties that are weaker than uniformly nonsquare but still possess the fixed point property in any Banach spaces. …”
mentioning
confidence: 52%
“…This result is related to the result of the paper by J. Falset et al 2006 by giving the examples and the motivation to find the geometric properties that are weaker than uniformly nonsquare but still possess the fixed point property in any Banach spaces. …”
mentioning
confidence: 52%
“…(c) Property M (X) >1 (see [12]). In particular this condition covers the uniformly nonsquare Banach spaces (see [13,14]). Other reflexive Banach spaces with M (X) >1 are those satisfying R(X) <2 (see [15]).…”
Section: Prus-szczepanik Condition (Ps)mentioning
confidence: 99%
“…Recently J. García-Falset, E. Llorens-Fuster and E.M Mazcuñan-Navarro have shown that uniformly non-square Banach spaces have the fixed point property (see [19]). Therefore, it was natural and interesting to look for criteria of non-squareness properties in various well-known classes of Banach spaces.…”
mentioning
confidence: 99%